Upaya Peningkatan Kreativitas dan Hasil Belajar Ekonomi Siswa Kelas XI IS 5 melalui Strategi Self Questioning and Answering Test di SMA Negeri 1 Lubuk Alung Kabupaten Padang Pariaman - Perkasa, Ripho Delzy (Jurusan PIPS FKIP UMMY Solok, 2017)
This study aimed to analyze the implementation of the strategy of self questioning and answering test. This research is a classroom action research. The object of this study is a class XI student of SMAN IIS 5 Lubuk Alung Padang Pariaman district. The data collected related to the creativity of students learning (observation and to look at improving student learning outcomes through the provision of a test). The data obtained were processed using the analysis and the mean percentage score. The results of the study in the first cycle, creativity and economic learning outcomes of students in learning the strategies that are in both criteria, creativity is still low currently on creativity indicators provide input to a friend at the time of the discussion has increased quite good. Student learning outcomes obtained an average of 69.85, with 20 students who got good grades of 33 students. In the second cycle has been an increase in both creativity and Economics student learning outcomes. To the creativity of student learning can be categorized on the criterion of good and very good, and for learning outcomes on the second cycle have gained an average of 81.06 with 28 students who got good grades of 33 students. Based on the findings, the authors suggest the teachers and principals to increase creativity and results for students at SMA Negeri I Lubuk Alung to make the strategy of self questioning and answering test combined with the provision of reinforcement and reward as an alternative learning strategies.